The Correlation between the Bone Morphotype and Density and Root Apical Resorption of the Anterior Teeth Due to Orthodontic Forces - Tsilosani, Nino; Natsvlishvili, Natia; Mirvelashvili, Ekaterine; Zerekidze, Tea (European Scientific Journal, ESJ, 2024)
The potential side effects of modern orthodontic treatment and its unfavorable impact on dentition and hard tissues have been extensively discussed in professional literature for decades. The presence of uncontrolled forces can result in pulp necrosis, radicular reabsorption, and/or loss of alveolar bone. Dehiscence and fenestration are more commonly found in anterior than posterior teeth, where only the periodontal ligament and the mucosa protect the dental root. Most studies investigating the effect of periodontal phenotype over gingival recession in orthodontic patients have primarily focused on examining the soft tissues. However, due to the vulnerability of thin alveolar bone, the previous evaluation of orthodontic candidate patients may also include the analysis of hard tissues. Bone density plays an important role in facilitating orthodontic tooth movement, such that reductions in bone density can significantly increase movement velocity. These types of localized density changes can affect the rate of orthodontic tooth movement and may also influence the risk of unwanted outcomes, such as the occurrence of dental external apical root resorption. According to the literature, the links of root resorption with the bone morphotype and the density are relevant in clinical dentistry but have not been studied in detail. However, the existing data is not yet conclusive.